The characteristics of lipases of psychrotrophic Yersinia, Enterobacter and Citrobacter spp. of dairy origin - SWARNA, C; PRABHA, R; SHANKAR, P A (The Indian Journal of Animal Sciences, 2013)
Psychrotrophic Yersinia.M18, Enterobacter M31 and Citrobacter M33 exhibited maximum growth and lipase activity on third day of incubation at 30oc. The lipase activity with Yersinia sp. was the highest at both pH 5.6 and pH 7.6. It was the highest at 7.6 and 7.0 with Enterobacler sp. and Citrobacter sp. respectively. The lipase of Yersinia and Enterobacter spp. was active in the temperature range of 7o to 40oc but the optimum temperature was at 30o to 40oC respectively. The lipase of Citrobacter sp. was active in the temperature range of 10o - 40oC with optimum activity at 30oC. EDT A treatment of the lipase activity of all the 3 cultures appreciably reduced their activity. However, all the divalent metal ions tested restored the activity of lipases of rersinia and Citrobacter. But the activity in Enterobacter lipase was not restored. Heating to above 70oC/10min completely destroyed the lipase activity of rersinia and Enterobacter while the activity of Citrobacter reduced to about 50% even after heating to 80oC/10min.